2009
DOI: 10.1159/000262312
|View full text |Cite
|
Sign up to set email alerts
|

Postendarterectomy Mortality in Octogenarians and Nonagenarians in the USA from 1993 to 1999

Abstract: Background: Relatively little is known about trends in the utilization or outcomes of carotid endarterectomy (CEA) in the very elderly. We determined trends in the rates of CEA and perioperative (in-hospital and 30-day) and long-term (1-, 2-, 3-, 4- and 5-year) mortality in a US national sample of patients ≧80 years of age. Methods: All fee-for-service Medicare patients (80–89 and ≧90 years of age) who had a CEA [ICD-9-CM (International Classification of Diseases, Ninth Revision, Clinical Modification): 38.12]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 78 publications
(99 reference statements)
0
7
0
1
Order By: Relevance
“…The by far largest cohort was reported by Lichtman et al . who analyzed data of all 140.376 patients older than 80 years undergoing CEA in the United States during a period of 6 years (1993-1999) [ 33 ]. They collected data on patients from their medical records.…”
Section: Resultsmentioning
confidence: 99%
“…The by far largest cohort was reported by Lichtman et al . who analyzed data of all 140.376 patients older than 80 years undergoing CEA in the United States during a period of 6 years (1993-1999) [ 33 ]. They collected data on patients from their medical records.…”
Section: Resultsmentioning
confidence: 99%
“…16 Analyses from administrative databases, probably not subject to publication bias as single-center studies may be, have often concluded that older patients suffer more complications than do younger patients and patients in prospective studies. 25,26 However, some of the data contributing to these latter studies are now >20 years old and are not likely to reflect current results after CEA. Furthermore, as noted before, many of the precedent studies are single-institution studies.…”
Section: Journal Of Vascular Surgerymentioning
confidence: 96%
“…Several larger studies have reported on outcomes after CEA in octogenarians in Western countries. 12,13 Rajamani et al 13 studied 4149 patients 70 years of age or older and found that patients aged 80-84 years had relatively good outcomes. However, that study did not show the outcome analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, that study did not show the outcome analysis. Lichtman et al 12 reported the perioperative and follow-up mortality rates of 140,376 patients 80 years of age or older who underwent CEA in the United States. They reported a perioperative mortality rate of 2.2% but did not indicate the causes of death or rate of death due to ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%